Review of the caddisfly genus Tagalopsyche with the description of new species and a related new genus (Trichoptera: Leptoceridae: Mystacidini) - Holzenthal, Ralph W.; Andersen, Trond (Zootaxa, 2007)
The long-horned caddisfly genus Tagalopsyche Banks, 1913 (Leptoceridae: Mystacidini) is reviewed and 4 new species are described and illustrated: T. apratita, new species (India), T. jolandae, new species (Brunei, Malaysia), T. kjaerandseni, new species (Ghana), and T. udagama, new species (India, Sri Lanka). The 4 previously described species are redescribed and illustrated: T. aethiopica Kimmins, 1963a (Ethiopia), T. brunnea (Ulmer, 1905) (Indonesia), T. fletcheri Kimmins, 1963b (India), and T. sisyroides Banks, 1913 (Indonesia, Philippines). A related new genus, Fernandoschmidia, new genus, and 2 new species, F. amudita, new species, and F. aramaniya, new species, from India are described and illustrated. The phylogenetic position of the new genus is assessed; it is sister to a clade formed by Tagalopsyche and Mystacides Berthold, 1827, the only other genus in the Mystacidini.